Mortality of Goshawks (Accipiter gentilis) Due to West Nile Virus Lineage 2 - Hubálek, Zdenek; Kosina, Marcel; Rudolf, Ivo; Mendel, Jan; Straková, Petra; Tomešek, Martin (Vector borne and zoonotic diseases (Larchmont, N.Y.), 2018)
In 2017, we isolated and identified West Nile virus (WNV) lineage 2 from two dead captive goshawks (Accipiter gentilis), for the first time in the Czech Republic. Goshawk might serve as an early indicator species for the ongoing WNV emergence in several European countries.
Keywords: virus západního Nilu; Falconiformes; Bird Diseases; Phylogeny; západonilská horečka; Animals, Wild; nemoci ptáků; avian disease; raptors; birds; divoká zvířata; Animals; central Europe; West Nile Fever; West Nile virus; Flavivirus; zvířata; fylogeneze